1984
DOI: 10.1016/0014-5793(84)80919-9
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of ferritin‐bound iron to adriamycin

Abstract: Interactions of adriamycin with ferritin-bound iron have been investigated. It is demonstrated (i) that adriamycin stimulates an iron-dependent lipid peroxidation in submitochondrial particles in the presence offerritin, and (ii) that incubation of adriamycin with ferritin results in a slow transfer of iron to adriamycin with formation of an adriamycin-iron complex. The results are discussed in relation to the possible role for intracellular iron in adriamycin toxicity. FerritinAdriamycin-Fe3+ complex Lipidper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

1986
1986
2003
2003

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 27 publications
0
14
1
Order By: Relevance
“…In contrast to our data, previous studies using isolated and purified ferritin have demonstrated that anthracyclines induce Fe release from this protein (Demant, 1984;Thomas and Aust, 1986). However, it is likely that the in vivo mechanisms involved in mobilizing Fe from ferritin are quite different from that observed with the purified protein.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our data, previous studies using isolated and purified ferritin have demonstrated that anthracyclines induce Fe release from this protein (Demant, 1984;Thomas and Aust, 1986). However, it is likely that the in vivo mechanisms involved in mobilizing Fe from ferritin are quite different from that observed with the purified protein.…”
Section: Discussioncontrasting
confidence: 99%
“…The IRPs are involved in post-translational regulation of various molecules involved in Fe metabolism, including ferritin and the TfR1 (Hentze and Kü hn, 1996;Richardson and Ponka, 1997). Several studies in vitro have also assessed the ability of anthracyclines to mobilize Fe from purified ferritin (Demant, 1984;Thomas and Aust, 1986;Gianni and Myers, 1992), Tf (Demant and Norskov-Lauritsen, 1986), and microsomal membranes (Minotti, 1990;Gianni and Myers, 1992). However, it is difficult to determine whether the Fe release observed from isolated and purified ferritin is physiologically relevant.…”
mentioning
confidence: 99%
“…There is evidence from several in vitro studies [3-l I] that these drug-metal ion complexes can act as redox catalysts in the formation of reactive and toxic oxygen species. In a previous report [12] we showed that ADM in vitro is capable of binding iron from the iron storage protein ferritin. We have extended this work to the interaction between ADM and the serum glycoprotein Tr involved in iron transport.…”
Section: Introductionmentioning
confidence: 99%
“…An enhancement of anthracycline activity upon metal complexation has already been described for iron in different experimental models, including erythrocyte ghost membranes (Myers et al 1982), submitochondrial particles (Demant 1984) and purified protein kinase C (Hannun et al 1989). The present data support the hypothesis that copper, as well as iron, is able to act as a catalyst for hydroxyl radical-producing Fenton reactions (Samuni et al 1984;Prtitz 1989).…”
Section: Resultsmentioning
confidence: 91%